Efficacy of Adding Sitagliptin to Ongoing Metformin on Metabolic Profile, Triglyceride-Glucose Index, Vitamin D3, and Liver Tests in Patients Type 2 Diabetes Mellitus and Nonalcoholic Fatty Liver Disease: A Double-Blind Randomized Clinical Trial - Habib Yaribeygi, PhD; Majid Ramezani, MD; Niki Katsiki, PhD, MD; Majid Mirmohammadkhani, PhD; Narges Sadat Tabaei, Msc (Current Therapeutic Research)
ABSTRACT: Background: Dipeptidyl peptidase-4 inhibitors provide potent antidiabetic effects in patients with type 2 diabetes mellitus (T2DM), but their role in the presence of nonalcoholic fatty liver disease (NAFLD) is not well-known. Objective: The aim of this clinical trial was to evaluate the effects of sitagliptin on the metabolic profile and liver test results in metformin-treated patients with T2DM and NAFLD. Methods: This was a prospective, 12-week, single-center, comparative randomized clinical trial enrolling 66 adult patients with T2DM and NAFLD (diagnosed by ultrasound). Patients were randomly assigned to either metformin (2000 mg/d, n = 33) or sitagliptin + metformin (100 and 2000 mg/d, respectively, n = 33), administered orally. Certain metabolic parameters, that is, fasting blood sugar (FBS), glycosylated hemoglobin, triglycerides (TGs), total cholesterol (TC), low-density lipoprotein cholesterol, vitamin D3 (vitD3), alkaline phosphatase, alanine aminotransferase (SGPT), and aspartate aminotransferase, were measured at baseline and after 12 weeks. Triglyceride-glucose (TG-G) index was also calculated. Results: All biochemical variables decreased by a greater extent in the sitagliptin + metformin group than in the metformin group, with differences in FBS (P = 0.030), TC (P = 0.017), TG (P = 0.008), SGPT (P = 0.018), and vitD3 (P = 0.001) reaching statistical significance. Furthermore, the mean reduction of the TG-G index was significantly greater in the sitagliptin + metformin group than in the metformin group (0.67 vs 0.21, respectively; P = 0.017). Conclusions: Sitagliptin + metformin therapy led to significantly greater improvements in FBS, TC, TG, SGPT, vitD3, and TG-G compared with the metformin monotherapy group. Other biomarkers also decreased more in the sitagliptin + metformin group than in the metformin group, but these differences did not reach statistical significance. The present findings should be interpreted with caution, although they suggest certain metabolic benefits after sitagliptin addition in metformin-treated patients with T2DM and NAFLD. Further studies are required to elucidate these effects and provide strong evidence for safe conclusions.